2022
DOI: 10.1111/dth.15913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between topical application of triamcinolone acetonide after fractional carbon dioxide laser versus microneedling in the treatment of resistant alopecia areata

Abstract: Alopecia areata (AA) is a disease that affects the psychological well‐being of the affected individuals. Laser‐assisted drug delivery and microneedling (MN) are promising methods for the treatment of different dermatological diseases. The aim of the study was to compare the efficacy of topical application of triamcinolone acetonide after fractional carbon dioxide laser versus MN in the treatment of resistant AA from a clinical and dermoscopic perspective. Thirty patients were randomly divided into two groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Black dot higher in microneedling group. No significant difference in effectiveness Laser group: no significant adverse effects Pain score significantly less in laser group ( p = 0.002) RCT/1 Omar et al [ 13 ] AA TAC (10 mg/ml) AFL (CO 2 ; Punto, DEKA, Italy) Power: 10 W Dwell time: 500 ms, Stack: 2 Spacing: 700 m 30 participants randomized to monthly laser or microneedling, followed by TAC until resolution or for a maximum of 6 sessions Both groups had a significant reduction in SALT score ( p < 0.001) with reduction in SALT higher in microneedling group than laser group ( p = 0.013) No statistically significant difference in side effects between groups. Only mild pain and erythema were reported RCT/2 Abd ElKawy et al [ 14 ] AA Clobetasol propionate AFL (ER: YAG; XS dynamics Fotona S1-121d, Ljubljana Slovenia) Fluence: 3 J/cm 2 Frequency: 3–5 Hz Mode: short pulse Spot size: 7 mm 30 subjects with AA had lesions randomized to LEADD or topical clobetasol alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black dot higher in microneedling group. No significant difference in effectiveness Laser group: no significant adverse effects Pain score significantly less in laser group ( p = 0.002) RCT/1 Omar et al [ 13 ] AA TAC (10 mg/ml) AFL (CO 2 ; Punto, DEKA, Italy) Power: 10 W Dwell time: 500 ms, Stack: 2 Spacing: 700 m 30 participants randomized to monthly laser or microneedling, followed by TAC until resolution or for a maximum of 6 sessions Both groups had a significant reduction in SALT score ( p < 0.001) with reduction in SALT higher in microneedling group than laser group ( p = 0.013) No statistically significant difference in side effects between groups. Only mild pain and erythema were reported RCT/2 Abd ElKawy et al [ 14 ] AA Clobetasol propionate AFL (ER: YAG; XS dynamics Fotona S1-121d, Ljubljana Slovenia) Fluence: 3 J/cm 2 Frequency: 3–5 Hz Mode: short pulse Spot size: 7 mm 30 subjects with AA had lesions randomized to LEADD or topical clobetasol alone.…”
Section: Resultsmentioning
confidence: 99%
“…Another comparative study for treatment resistant AA compared microneedling or AFL (CO 2 ), both followed by application of triamcinolone acetonide (TAC). Both groups had significant improvement at each follow-up with the only significant difference between groups being the presence of black dot dermoscopy sign which was more present in the laser group (46.7 vs. 13.3%) [ 13 ]. Two small case series of LEADD with TAC for AA using AFL (CO 2 ), and RFMN saw positive results [ 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a case–control, single‐blind study including 30 patients with AA, hair regrowth rates in a 1540 nm fractional erbium‐glass laser treatment group and the control group were 30% and 6.45%, respectively 55 . A study of 30 patients with AA demonstrated terminal hair regrowth in the fractional carbon dioxide laser and microneedling groups (33.3% and 46.7%, respectively) 56 …”
Section: Progress In Treatments (Excluding For Jak Inhibitors)mentioning
confidence: 98%
“…55 A study of 30 patients with AA demonstrated terminal hair regrowth in the fractional carbon dioxide laser and microneedling groups (33.3% and 46.7%, respectively). 56 A study of 41 patients with AA demonstrated comparable ≥50%…”
Section: Weeksmentioning
confidence: 99%
“…They are also being explored as solutions for the treatment of other types of hair loss, including scarring alopecia [47]. More recently, there has been increased interest in the use of fractional ablative lasers to facilitate the delivery of topical treatments (i.e., laser-assisted drug delivery) such as minoxidil, platelet-rich plasma, and various growth factors, thereby enhancing their penetration and efficacy [43,48,49]. However, fractional lasers are not yet approved as treatments for any type of alopecia, and it is likely that their role in the treatment of alopecias will evolve as a complement to enhance the administration and efficacy of standard treatments [42].…”
Section: Fractional Lasersmentioning
confidence: 99%